Memoirs of the reign of George III - Belsham, William (Joseph Addison Alexander library., 1795)
Vols. 1-4, To the session of Parliament ending A.D. 1793. -- v. 5-6, To the commencement of the year 1799. -- v. 7-8, To the conclusion of the Treaty of Amiens, 1802. -- v. 9-10, From the Treaty of Amiens, A.D. 1802, to the termination of the regency, A.D. 1820.